2019
DOI: 10.1016/j.ijdevneu.2019.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Early adversity, child neglect, and stress neurobiology: From observations of impact to empirical evaluations of mechanisms

Abstract: Research on the effects of early life adversity, and in particular on the absence of responsive caregiving, has shown long‐term impacts on well‐being and development. These investigations have been conducted both in human populations and in animal models. The work has demonstrated that neglect experienced in the early years can affect not only behavior but also neurobiological functioning. In particular, studies of children in the foster care system show convergence with research on children adopted following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 80 publications
(122 reference statements)
0
15
0
1
Order By: Relevance
“…16 Neglect is associated with short-term and long-term effects on children's cognitive, socioemotional, and behavioral development. 17,18 Neglect that occurs early in life can have more profound effects on development.…”
Section: Introductionmentioning
confidence: 99%
“…16 Neglect is associated with short-term and long-term effects on children's cognitive, socioemotional, and behavioral development. 17,18 Neglect that occurs early in life can have more profound effects on development.…”
Section: Introductionmentioning
confidence: 99%
“…Biological embedding such as alterations in brain structure, function, connectivity, and epigenetic programming has been consistently reported in individuals exposed to adversities in childhood [2,3]. It has been suggested that exposure to ELS could modify the trajectories of brain maturation [4][5][6], increasing vulnerability to psychopathologies later in life. However, neurobiological mechanisms underlying the emergence of these changes have been poorly characterized.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ELS affects not only brain function and behavior, but it can lead to dysregulated neurochemical, neuroendocrine, and immune responses during adulthood. In particular, childhood abuse and parental neglect increase adult inflammatory responses and alters neuroendocrine stress responses mediated by the hypothalamic-pituitary-adrenal (HPA) axis [ 3 , 6 , 8 , 9 , 10 , 11 ]. Moreover, studies using animal models of ELS like prolonged maternal separation (MS) in rodents (in which the offspring are daily separated from their mothers before weaning) have been shown to alter adult brain monoamine levels in several brain regions related with abnormal behavior, like dopamine, serotonin, and norepinephrine [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%